الإسراء والمعراج في الشعر العربي (دراسة موازنة بين البوصيري وأحمد شوقي): Isra and Mikraj in Arabic Poetry (A Comparative Study between Al-Busiri and Ahmed Shawqi) - Khulqi, Aghnin; Zahasfan , Alvian Iqbal; Tsaqofi, Waki Ats; Mahfuzo, Muhammad Rizal (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2024)
The aim of this research is to compare the story of Isra Mikraj in two poems by Al-Bushiri entitled Burdah and al-Hamziyah with two poems by Ahmad Syauqi entitled Nahj al-Burdah and al-Hamziyah al-Nabawiyah in terms of form and content, and to reveal the concept of Isra Mikraj according to the two poets. This research is a qualitative research using interpretation approach. Comparative studies in this research were conducted by comparing literary works based on the same theme, and revealing affinities, historical aspects and influences. The results of the research found that Ahmad Syauqi was greatly influenced by Al-Bushiri. Kasidah al-Hamziyah Al-Bushiri and al-Hamziyah al-Nabawiyah Ahmad Syauqi, in terms of form, both have similarities in using beautiful language although there are differences because Ahmad Syauqi is more diverse in choosing diction. Likewise, in terms of form, Burdah Al-Bushiri and Nahj al-Burdah Ahmad Syauqi have similarities in using beautiful language, even though they have differences in terms of imagination. Meanwhile, in terms of content, all of them have similarities in believing in the story of Isra' Mi'raj, even though the concept of Isra' Mi'raj according to Al-Bushiri and Ahmad Syauqi is different. According to Al-Bushiri, the concept of Isra Mikraj is a miracle, a lesson in faith, and Islamic teachings such as patience and love for the Prophet. Meanwhile, according to Ahmad Syauqi, the concept of Isra Mikraj is an event that raises rationality debates, an event that has a lot of lessons and knowledge, obligatory prayer, and a message about the important role of the Al-Aqṣa Mosque in Palestine. ملخص يهدف هذا البحث إلى مقارنة قصة الإسراء والمعراج في قصيدتين للبوصيري بعنوان البردة والهمزية، مع قصيدتين لأحمد شوقي بعنوان نهج البردة والهمزية النبوية من حيث الشكل والمضمون، والكشف في قصيدتين للبوصيري بعنوان البردة والهمزية مع قصيدتين لأحمد شوقي بعنوان نهج البردة والهمزية النبوية عن مفهوم الإسراء المعراج حسب الشاعرين لهما خلفيات مختلفة. يتم تضمين هذا البحث في البحث النوعي باستخدام الدراسة المكتبية. ويتم إجراء الدراسة الموازنة في هذا البحث من خلال مقارنة الأعمال الأدبية التي تحمل الموضوع في نفسه، وكشف التشابهات والاختلافات، والعوامل التاريخية، والتأثير والتأثر. تثبت نتائج هذا البحث أن أحمد شوقي كان متأثرا بالبوصيري. أما قصيدة الهمزية للبوصيري والهمزية النبوية لأحمد شوقي، فكلاهما يتشابهان في الشكل في استخدام اللغة الجميلة، وإن كان هناك اختلاف لأن أحمد شوقي أكثر تنوعا في اختيار المفردات. وكذلك من حيث الشكل، فإن بردة البوصيري ونهج البردة لأحمد شوقي يتشابهان في استخدام اللغة الجميلة، رغم أن بينهما اختلافات من حيث الخيال. أما من حيث المضمون، فكلها تتشابه في الاعتقاد بقصة الإسراء المعراج، مع أن مفهوم الإسراء المعراج عند البوصيري وأحمد شوقي مختلف. وبحسب البوصيري، فإن مفهوم الإسراء والمعراج هو معجزة، ودرس في الإيمان، وتعاليم إسلامية مثل الصبر ومحبة النبي. أما بالنسبة لأحمد شوقي، فإن مفهوم الإسراء المعراج هو حادثة يثير مناظرات عقلانية، وحادثة فيها الكثير من العبر والمعرفة، حادثة وجوب الصلاة، ورسالة حول أهمية المسجد الأقصى في فلسطين. Abstrak Tujuan dari penelitian ini adalah membandingkan kisah Isra Mikraj dalam dua syair Al-Bushiri yang berjudul Burdah dan al-Hamziyah dengan dua syair karya Ahmad Syauqi yang berjudul Nahj al-Burdah dan al-Hamziyah al-Nabawiyah dari sisi bentuk dan konten, serta mengungkap konsep Isra Mikraj menurut kedua penyair tadi. Penelitian ini termasuk dalam penelitian kualitatif dengan menggunakan kajian pustaka. Kajian perbandingan dalam penelitian ini dilakukan dengan cara membandingkan karya sastra berdasarkan tema yang sama, dan mengungkap afinitas, aspek historis, dan keterpengaruhan. Hasil dari penelitian ditemukan bahwa Ahmad Syauqi mendapat banyak pengaruh dari Al-Bushiri. Kasidah al-Hamziyah Al-Bushiri dan al-Hamziyah al-Nabawiyah Ahmad Syauqi, dari segi bentuk keduanya memiliki kesamaan dalam menggunakan bahasa yang indah walaupun terdapat perbedaan karena Ahmad Syauqi lebih beragam dalam memilih diksi. Begitu pula dalam kasidah Burdah Al-Bushiri dan Nahj al-Burdah Ahmad Syauqi dari segi bentuk memiliki kesamaan dalam menggunakan bahasa yang indah, walaupun memiliki perbedaan dalam hal imajinasi. Sedangkan dari segi konten semuanya memiliki kesamaan dalam mempercayai kisah Isra Mikraj, walaupun konsep isra’ mikraj menurut Al-Bushiri dan Ahmad Syauqi berbeda. Konsep Isra Mikraj menurut Al-Bushiri adalah mukjizat, pelajaran iman, serta ajaran Islam seperti tentang kesabaran dan cinta kepada Nabi. Sedangkan konsep Isra Mikraj menurut Ahmad Syauqi adalah peristiwa yang menimbulkan perdebatan rasionalitas, peristiwa yang memiliki banyak pelajaran dan pengetahuan, pewajiban salat, dan pesan peran penting Masjid Al-Aqṣa di Palestina.